Profiles of tobacco product use and related consumer characteristics in the US and Israel: A multiple-group latent class analysis - Yan Wang; Cassidy R. LoParco; Yuxian Cui; Zongshuan Duan; Yael Bar-Zeev; Hagai Levine; Lorien C. Abroms; Amal Khayat; Carla J. Berg (Taylor & Francis Group, 2023)
Despite tobacco marketing diversification, limited research has examined use profiles across countries, particularly in relation to consumer values (e.g. appeal of innovation, conscientiousness). Using 2021 data, latent class analysis assessed past-month use of seven tobacco products (cigarettes, electronic cigarettes [e-cigarettes], heated tobacco products, cigars, hookah, pipe, smokeless) among adults reporting past-month use in the United States (US n = 382) and Israel (n = 561). Multivariable multinomial regression examined consumer values and sociodemographics in relation to country-specific class membership. US classes included: primarily cigarette 58.1%; e-cigarette-no cigarette 17.5%; primarily cigar 14.9%; and poly-product 9.9%. Higher innovation correlated with e-cigarette-no cigarette and poly-product (vs. primarily cigarette) use. Other correlates included being: younger with e-cigarette-no cigarette; male, Black, and more educated with primarily cigar; and Black and Asian (vs. White) with poly-product. Israel classes included: primarily cigarette 39.0%; moderate poly-product 40.3%; high poly-product 13.4%; and hookah 7.3%. Lower conscientiousness correlated with moderate poly-product (vs. primarily cigarette) use; higher innovation correlated with high poly-product; lower innovation correlated with hookah. Other correlates included being: younger, male, and more educated with moderate poly-product; male and sexual minority with high poly-product; and Arab with hookah. Tobacco consumer segments within and across countries likely reflect different consumer values and industry marketing targets.